Differential associations of abdominal visceral, subcutaneous adipose tissue with cardiometabolic risk factors between African and European Americans. (11th February 2014) - Liu, Jiankang; Coady, Sean; Carr, J. Jeffery; Hoffmann, Udo; Taylor, Herman A.; Fox, Caroline S.
<x xml:space="preserve">Abstract</x> Objective To examine the relative association of abdominal visceral adipose tissue (VAT) with cardiometabolic risk factors between African and European Americans. Methods A cross‐sectional study of 2, 035 African Americans from the Jackson Heart Study (JHS) and 3, 170 European Americans from the Framingham Heart Study (FHS) who underwent computed tomography assessment of VAT and subcutaneous adipose tissue (SAT) was conducted. The FHS participants were weighted to match the age distribution of the JHS participants, and the metabolic risk factors were examined by study groups in relation to VAT. Results JHS participants had higher rates of obesity, hypertension, diabetes, and metabolic syndrome than FHS participants (all P = 0.001). The associations were weaker in JHS women for VAT with blood pressure, triglycerides, HDL‐C, and total cholesterol (Pinteraction = 0.03‐0.001) than FHS women. In contrast, JHS men had stronger associations for VAT with high triglycerides, low HDL, and metabolic syndrome (all Pinteraction = 0.001) compared to FHS men. Similar associations and gender patterns existed for SAT with most metabolic risk factors. Conclusions The relative association between VAT and cardiometabolic risk factors is weaker in JHS women compared to FHS women, whereas stronger associations with triglycerides and HDL were observed in JHS men.